Equivariant geometry of singular cubic threefolds - Ivan Cheltsov; Yuri Tschinkel; Zhijia Zhang (Forum of Mathematics, Sigma)
We study linearizability of actions of finite groups on singular cubic threefolds, using cohomological tools, intermediate Jacobians, Burnside invariants, and the equivariant Minimal Model Program.